2019
DOI: 10.1002/humu.23738
|View full text |Cite
|
Sign up to set email alerts
|

UniProt genomic mapping for deciphering functional effects of missense variants

Abstract: Understanding the association of genetic variation with its functional consequences in proteins is essential for the interpretation of genomic data and identifying causal variants in diseases. Integration of protein function knowledge with genome annotation can assist in rapidly comprehending genetic variation within complex biological processes. Here, we describe mapping UniProtKB human sequences and positional annotations, such as active sites, binding sites, and variants to the human genome (GRCh38) and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Second, we investigated whether the distributions of UNEECON scores varied across different types of protein regions annotated by UniProt [47,49] and MobiDB [48]. We observed that the distributions of UNEECON scores were similar among α-helices, β-strands, and hydrogen-bonded turns (Fig 2b).…”
Section: Uneecon Scores Capture Variation Of Negative Selection Withimentioning
confidence: 96%
See 2 more Smart Citations
“…Second, we investigated whether the distributions of UNEECON scores varied across different types of protein regions annotated by UniProt [47,49] and MobiDB [48]. We observed that the distributions of UNEECON scores were similar among α-helices, β-strands, and hydrogen-bonded turns (Fig 2b).…”
Section: Uneecon Scores Capture Variation Of Negative Selection Withimentioning
confidence: 96%
“…(b) Distributions of UNEECON scores estimated for potential missense mutations in various protein regions. The functional sites and protein secondary structures are based on UniProt annotations [47]. The predicted disordered protein regions are from MobiDB [48].…”
Section: Uneecon Scores Accurately Predict Missense Mutations Associamentioning
confidence: 99%
See 1 more Smart Citation
“…Clusters containing Ն4 members were analyzed further. Cluster representatives were annotated using protein profile searches against three databases: the Pfam-A database using HMMER3 (using family-specific gathering thresholds) (49), the NCBI Conserved Domain Database using RPS-BLAST (E value Ͻ 0.01) (51)(52)(53), and the Uniprot30 database (accessed February 2019, available from http://wwwuser.gwdg.de/~compbiol/data/hhsuite/databases/hhsuite_dbs/) using HHblits (54,55). Multiple sequence alignments were automatically generated from three iterations of the HHblits search and used for profile-profile comparisons against the PDB70 database (HHpred probability Ͼ 90, accessed February 2019, available from http://wwwuser.gwdg.de/~compbiol/data/hhsuite/ databases/hhsuite_dbs/).…”
Section: Methodsmentioning
confidence: 99%
“…Clusters containing ≥ 4 members were analyzed further. Cluster representatives were annotated using protein-profile searches against three databases: the Pfam-A database using HMMER3 (El-Gebali et al, 2019), the NCBI Conserved Domain Database using RPS-BLAST (Marchler-Bauer et al, 2017, 2011; Marchler-Bauer and Bryant, 2004), and the Uniprot30 database (accessed February 2019, available from http://www.user.gwdg.de/~compbiol/data/hhsuite/databases/hhsuite_dbs/) using HHblits (McGarvey et al, 2019; Remmert et al, 2012). Multiple sequence alignments were automatically generated from three iterations of the HHblits search and used for profile-profile comparisons against the PDB70 database (accessed February 2019, available from http://www.user.gwdg.de/~compbiol/data/hhsuite/databases/hhsuite_dbs/).…”
Section: Methodsmentioning
confidence: 99%